Clinical diagnosis and alternative surgical treatment of tetralogy of Fallot in a dog. A case report - Larsson,M.H.M.A (2000)
Tetralogy of Fallot was diagnosed in a 30 month-old Cocker Spaniel female, through physical, radiographic, electrocardiographic, and echocardiographic exams. The animal was submitted to a palliative surgical correction, the Blalock-Taussig technique, and 46 months after the surgery, no signs of cardiopulmonary decompensation were observed.